2020
DOI: 10.21203/rs.3.rs-40156/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examination of the Exchange Rate and Import Price Pass-through to Inflation: A View from Nigeria

Abstract: Abstract We examine the effect of exchange rate and import price pass-through to inflation in Nigeria using headline inflation and import price data, with the aid of a non-recursive Structural Vector Autoregression model. Our results indicate mostly incomplete ERPT and IPPT to inflation. Specifically, we found that (i) the ERPT to the INF is incomplete at all horizons. (ii) IPPT to the INF is incomplete at all horizons. (iii) IPPT to inflation is relatively more rapid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…The coefficients of the exchange rate, which are less than one, suggest that ERPT to import and consumer prices is incomplete, indicating that changes in exchange rates are not entirely mirrored in the prices of imported goods and services and in the prices paid by consumers. The present findings are consistent with prior research conducted by [30][31][32][33], which similarly reported an incomplete ERPT effect on consumer prices in Nigeria. Empirical evidence suggests that the elasticity of ERPT to import prices is greater than that of ERPT to consumer prices.…”
Section: Discussion Of the Resultssupporting
confidence: 93%
“…The coefficients of the exchange rate, which are less than one, suggest that ERPT to import and consumer prices is incomplete, indicating that changes in exchange rates are not entirely mirrored in the prices of imported goods and services and in the prices paid by consumers. The present findings are consistent with prior research conducted by [30][31][32][33], which similarly reported an incomplete ERPT effect on consumer prices in Nigeria. Empirical evidence suggests that the elasticity of ERPT to import prices is greater than that of ERPT to consumer prices.…”
Section: Discussion Of the Resultssupporting
confidence: 93%